The 23rd midnight - Patterson, James, 1947-; Paetro, Maxine (New York : Little, Brown and Company, 2023)
Detective Lindsay Boxer put serial killer Evan Burke in jail. Reporter Cindy Thomas wrote a book that put him on the bestseller list. An obsessed maniac has turned Burke's true-crime story into a playbook. And is embellishing it with gruesome touches all his own. Now Lindsay's tracking an elusive suspect, and the entire Murder Club is facing destruction.
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Women's Murder Club (Imaginary organization) -- Fiction; Copycat crimes -- Fiction; Murder -- Investigation -- Fiction; Serial murderers -- Fiction; Large type books; Detective and mystery fiction